EU Regular Economic Report, Fall 2015 : Sustaining Recovery, Improving Living Standards - World Bank Group (World Bank, Washington, DC, 2016)
The European Union (EU) Regular Economic Report (RER), is a semiannual publication of the World Bank Group and covers economic developments, prospects, and economic policies in the European Union. The report uses four sub-groups that share broadly similar development patterns EU : Central Europe comprises Bulgaria, Croatia, Czech Republic, Hungary, Poland, Romania, Slovak Republic and Slovenia; Northern Europe comprises Denmark, Estonia, Finland, Latvia, Lithuania and Sweden; Southern Europe comprises Cyprus, Greece, Italy, Portugal and Spain; Western Europe comprises Austria, Belgium, France, Germany, Ireland, Luxembourg, the Netherlands and the United Kingdom. While the report covers the European Union, it provides additional information on European countries which had historically a stronger operational engagement with the World Bank Group, in particular, Bulgaria, Croatia, Poland and Romania. The focus note of this RER covers “Welfare States and the Protection of the Poor in the European Union”.